The first discovery of Tc1 transposons in yeast - Chang, Jia; Duan, Guangyou; Li, Wenjing; Yau, Tung On; Liu, Chang; Cui, Jianlin; Xue, Huaijun; Bu, Wenjun; Hu, Yanping; Gao, Shan (Frontiers in Microbiology, 2023)
Background Identification of transposons without close homologs is still a difficult task. IS630/Tc1/mariner transposons, classified into a superfamily, are probably the most widespread DNA transposons in nature. Tc1/mariner transposons have been discovered in animals, plants, and filamentous fungi, however, not in yeast. Results In the present study, we report the discovery of two intact Tc1 transposons in yeast and filamentous fungi, respectively. The first one, named Tc1-OP1 (DD40E), represents Tc1 transposons in Ogataea parapolymorpha. The second one, named Tc1-MP1 (DD34E), represents Tc1 transposons in the Rhizopodaceae and Mucoraceae families. As a homolog of Tc1-OP1 and Tc1-MP1, IS630-AB1 (DD34E) was discovered as an IS630 transposon in Acinetobacter spp. Conclusion Tc1-OP1 is not only the first reported Tc1 transposon in yeast, but also the first reported nonclassical Tc1 transposon. Tc1-OP1 is the largest of IS630/Tc1/mariner transposons reported to date and significantly different from others. Notably, Tc1-OP1 encodes a serine-rich domain and a transposase, extending the current knowledge of Tc1 transposons. The phylogenetic relationships of Tc1-OP1, Tc1-MP1 and IS630-AB1 indicated that these transposons had evolved from a common ancestor. Tc1-OP1, Tc1-MP1 and IS630-AB1 can be used as reference sequences to facilitate the identification of IS630/Tc1/mariner transposons. More Tc1/mariner transposons will be identified in yeast, following our discovery.